GAYA KEPEMIMPINAN, BUDAYA, DAN KOMPETENSI TERHADAP KEPUASAN KERJA DAN KINERJA GURU SMP SWASTA ISLAM - Vinnafatun, Vinnafatun; Fathorrahman, Fathorrahman; Bukhori, Mohammad (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
This research is to describe the effect of headmaster’s leadership style on teacher’s satisfaction and on teacher’s performance, the effect of school culture on teacher’s satisfaction and on teacher’s performance, the effect of teacher competence on teacher’s satisfaction and on teacher’s performance, the effect of teacher’s satisfaction on teacher’s performance. And also the indirect effect is the effect of headmaster’s leadership style on teacher’s performance through teacher’s satisfaction, the effect of school culture on teacher’s performance through teacher’s satisfaction, and the effect of teacher performance on teacher’s performance through teacher’s satisfaction. The samples are teachers from eleven Private Islamic Junior High School in Malang City. Analysis method is descriptive analysis and Statistic analysis is Partial Least Square technique analysis which using smartPLS 3.0 programme.The result of this research is headmaster’s leadership style influence on teacher’s satisfaction, headmaster’s leadership style do not influence on teacher’s performance, school culture do not influence on teacher’s satisfaction, school culture influence on teacher’s performance, teacher competence influence on teacher’s satisfaction, teacher competence influence on teacher’s performance, teacher’s satisfaction do not influence on teacher’s performance. Teacher’s satisfaction is not be mediate the effect between headmaster’s leadership style, school culture, and teacher competence on teacher’s performance.